INDONESIA TOURISM MARKETING IN SOUTH KOREA - Sophia, Bella; Safitri, Karin Amelia (UI Scholars Hub, 2019)
This paper describes the analysis of Indonesian tourism marketing process in the Repubic of Korea. The analysis started from the preparation process up till the implementation process; such as product instrument, instrument distribution, promotion instrument, public relations, and evaluation. It is revealed the obstacles of tourism marketing process the which has been done. Those are the lack of human resources, lack of marketing funds, and closed Korea Busan Indonesia Center. It also Explains the strategy of tourism marketing to increase of the number of Korean tourists to visit the country. Qualitative research was conducted in this final paper. The result of analysis shows that Indonesian tourism marketing in the Republic of Korea has not been done well because of the lack of human resources and the lack of the marketing funds.